2021
DOI: 10.22541/au.163479188.80550750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

End-of-life home care during the COVID-19 pandemic

Abstract: Patients and their families are discouraged from the restrictions on hospital visits for coronavirus Infection control. This separation might further deteriorate the mental health of both vulnerable patients and their family members. Home care could be a preferable solution to this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Home care became a necessity in Japan, particularly during COVID‐19 when there is a constant rise in cases, difficult hospitalization, and a shortage of health workers and beds. 6 However, while emphasizing the importance of home care, it is equally important to expand home care measures, particularly during the COVID‐19 pandemic, as underlined by this case.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Home care became a necessity in Japan, particularly during COVID‐19 when there is a constant rise in cases, difficult hospitalization, and a shortage of health workers and beds. 6 However, while emphasizing the importance of home care, it is equally important to expand home care measures, particularly during the COVID‐19 pandemic, as underlined by this case.…”
Section: Discussionmentioning
confidence: 97%
“… 5 Studies have reported the importance of end‐of‐life home care during COVID‐19. 6 While it could seem an effective option, it is necessary to understand, acknowledge, and be prepared for possible challenges that may arise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation